Meniup Super Bubbles dan Baling-Baling Bamboo pada Anak Penderita Pneumonia - Padila Padila; Harsismanto J; Lussyefrida Yanti; Setiawati Setiawati; Juli Andri (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effect of blowing superbubbles and blowing bamboo propellers on children's respiratory frequency with pneumonia. The study design was pre-test and post-test two groups. The results of the univariate analysis before the blow therapy were carried out. Super bubbles, the respiratory frequency of all respondents was included in the moderate category, namely 10 (100%) respondents. After the intervention, there was a change to the mild type, namely as many as 3 (30%) respondents. Whereas before the therapy of blowing bamboo propellers, the respiratory frequency of the majority of respondents was included in the medium category, namely as many as 8 (80%) of respondents, and after therapy, the respiration frequency was balanced between the moderate and light types, namely as many as 50% of respondents respectively. The bivariate analysis results showed the effect of blowing superbubbles and blowing bamboo propellers on the respiratory frequency of the children with a p-value of 0.000, and 0.006, respectively. In conclusion, the intervention of blowing superbubbles and blowing propeller affects the respiratory frequency of children with pneumonia. Keywords: Baling-Baling Bamboo, Respiratory Frequency, Blow Super Bubbles